Pipeline lateral gas flow modelling and impedance matching. (2016) - Whalley, Robert; Abdul-Ameer, Alaa
The flow of gas in long pipelines is considered. Distributed parameter modelling methods are advocated for the pipeline whilst lumped analysis techniques are employed for the relatively concentrated assemblies such as the compressors, input and exit valves, bends and pipeline branches. Gas stream energy storage and the series and shunt, frictional resistance, energy dissipation effects are included in the multivariable analysis procedure. The response characteristics of the system are computed following voltage changes on the compressor motor. The optimum, 'matched', input and exit, pipeline impedance values are derived, maximising thereby the steady state exit volume flow whilst minimising the constrained input-exit volume flow difference with respect to the pipeline roughness parameter. Application studies are presented. The transient response of the pipeline system with the optimum and arbitrarily selected impedance values are computed validating the optimisation analysis and theoretical predictions herein.